2018
DOI: 10.3389/fendo.2018.00396
|View full text |Cite
|
Sign up to set email alerts
|

Critical Enzymatic Functions of FTO in Obesity and Cancer

Abstract: Fat mass and obesity-associated protein (FTO) single-nucleotide polymorphisms (SNPs) have been linked to increased body mass and obesity in humans by genome-wide association studies (GWAS) since 2007. Although some recent studies suggest that the obesity-related SNPs in FTO influence obesity susceptibility likely through altering the expression of the adjacent genes such as IRX3 and RPGRIP1L, rather than FTO itself, a solid link between the SNP risk genotype and the increased FTO expression in both human blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 102 publications
1
96
0
10
Order By: Relevance
“…Many studies have demonstrated that dysregulated m6A modification is associated with human diseases such as obesity, type 2 diabetes mellitus, and infertility (27)(28)(29). In addition, the dysregulated expression of m6A-related genes is closely related to multiple tumors, including OS.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that dysregulated m6A modification is associated with human diseases such as obesity, type 2 diabetes mellitus, and infertility (27)(28)(29). In addition, the dysregulated expression of m6A-related genes is closely related to multiple tumors, including OS.…”
Section: Discussionmentioning
confidence: 99%
“…Milk consumption has been linked with increased expression of fat mass and obesity-associated gene (FTO) via miR-148a-mediated suppression of DNMT1 [327]. Epidemiology studies show that FTO SNPs (including rs9939609, rs17817449, rs8050136, rs1477196, rs6499640, rs16953002, rs11075995, and rs1121980) are associated with increased FTO expression, overweight/ obesity and increased risk of various types of cancers, including PCa [328]. FTO has recently been shown to increase the expression of C/EBPα and C/EBPβ [329,330], which are upregulated in PCa tissue [331][332][333].…”
Section: Prostate Cancermentioning
confidence: 99%
“…FTO has been functionally implicated in both adipogenesis and tumorigenesis and on the underlying m 6 A-dependent demethylase activity which influences several mRNA processing events (Gerken et al, 2007;Bartosovic et al, 2017;Deng et al, 2018). The most notable genetic variants from FTO associated with obesity and body composition traits are a cluster of at least 20 common SNPs from its first intron (Loos and Yeo, 2014).…”
Section: Introductionmentioning
confidence: 99%